Kool skools student making music - Donato, Aaron Firth; McKenzie, Lachlan; De Robbie, Michael; Classroom Video (Australia : Classroom Video, 2007)
This program looks at how the Kool Skools project encourages a broad range of musical project in schools and other youth organisations. Profiling three different Kool Skools musical projects, the program features rock, jazz and chamber music and is an access-all-areas pass into this inspiring new project
Title from title screen
Executive producer, Mark McAuliffe
Voice over: Kellie Jones
DVD Format
Keywords: Composition (Music); Rock music; Jazz music; Chamber music